Design and data analysis for a belt-for-blind for visual impaired people - Hossain, Eklas; Khan, Md. Raisuddin; Ali, Ahad (Inderscience Publishers, 2011)
This research designs a new walking support system for the blind people in order to navigate without any assistance from others or using any guide cane. With the help of this device, a user can move independently and able to walk freely almost like a normal person. In this research, a belt for blind wearable around the waist is equipped with four ultrasonic sensors and one sharp infrared sensor. A mathematical model has been developed based on the specifications of the ultrasonic sensors to identify optimum orientation of the sensors for detecting stairs and holes. These sensors are connected to a microcontroller along with a laptop so that we can get sufficient data for analysing terrain on the walkway of the blind. Based on the analyses of the acquired data, we have developed an algorithm capable of classifying various types of obstacles. The developed belt for blind device is superior in terms of less weight less, able to detect stair and hole, low cost, less power consumption, adjustable, less training and availability of actuation systems. It was tested and implemented successfully to address all those issues.